Tanggapan Masyarakat di Media Sosial (Twitter) Tentang Kebijakan Penghapusan Ujian Nasional - Novia Fatimatuzzahra; Dea Avinindya Puspita; Dian Suluh Kusuma D (Fakultas Ilmu Sosial dan Ilmu Politik, 2019)
Social media has now become a place for the wider community to channel all aspirations and complaints related to many things. In addition, social media is also used by the government as a tool to communicate with the people as well as a medium to broadcast information about a new policy. One of them is about the new policy of eliminating national exams which has recently become a lively subject among social media users, especially Twitter. This article was written with the aim to find out the opinions and controversies that occurred on Twitter social media after the issuance of a policy on the elimination of the national exam (UN). There are many pros and cons but many Twitter users respond to this with jokes. Using qualitative research methods by means of content analysis. By understanding, identifying, and processing a document to understand the meaning contained therein.